Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1. A = (-2)(-3) - 5.|-5| + 125.\(\left(-\dfrac{1}{5}\right)^2\)
= 6 - 25 + 125.\(\dfrac{1}{25}\)
= -19 + 5
= -14
@Shine Anna
#)Giải :
a) \(A=\frac{4^5.9^4-2^6.6^9}{2^{10}.3^8+6^8.20}=\frac{2^{10}.3^8-2^{10}.3^8.3}{2^{10}.3^8+2^8.3^8.2^2.5}=\frac{2^{10}.3^8-2^{10}.3^8.3}{2^{10}.3^8+2^{10}.3^8.5}=\frac{2^{10}.3^8\left(1-3\right)}{2^{10}.3^8\left(1+5\right)}=-\frac{1}{3}\)
\(a,A=\frac{2^{10}.3^8-2^{10}.3^9}{2^{10}.3^8+2^{10}.3^8.5}\)
\(=\frac{2^{10}.3^8\left(1-3\right)}{2^{10}.3^8\left(1+5\right)}=\frac{-1}{3}\)
Học tốt!!!!!!!!!!!!!
a) \(\frac{\left(5.2\right)}{3.2}-\frac{1}{2}x+\frac{1}{3}+\frac{1}{5}=\frac{\left(3.2\right)}{5}\)
\(\Leftrightarrow\)\(\frac{1}{2}-\frac{1}{2}x+\frac{8}{15}=\frac{6}{5}\)
\(\Leftrightarrow\)\(\frac{1}{2}-\frac{2}{3}=\frac{1}{2}x\)
\(\Leftrightarrow\)\(-\frac{1}{6}=\frac{1}{2}x\)
\(\Leftrightarrow\)x=-1/3
b) VT= \(\frac{\left(3.5.4.2\right)}{5.2.3}=4\)
\(\Leftrightarrow\left(x-\frac{1}{2}\right):6+4=4:\frac{2}{3}=6\)
\(\Leftrightarrow\left(x-\frac{1}{2}\right):6=2\)
\(\Leftrightarrow x-\frac{1}{2}=12\)
=> x= 12,5
a)
4 . 25 – 12 . 25 + 170 : 10
= (4 . 25) – (12 . 25) + (170 : 10)
= 100 - 300 + 17
= -183
b)
(7 + 33 + 32) . 4 – 3
= (7 + 27 + 9) .4 – 3
= 43 . 4 – 3
= (43 . 4) – 3
= 45
c)
12 : {400 : [500 – (125 + 25 . 7)}
= 12 : {400 : [500 – (125 + 175)}
= 12 : (400: 200)
= 12 : 2
= 6
d)
168 + {[2.(24 + 32) - 2560] : 72}.
= 168 + [2 . (16 + 9) – 1] : 49
= 168 + 49: 49
= 168 + 1
= 167
a)
4 . 25 – 12 . 25 + 170 : 10
= (4 . 25) – (12 . 25) + (170 : 10)
= 100 - 300 + 17
= -183
b)
(7 + 33 + 32) . 4 – 3
= (7 + 27 + 9) .4 – 3
= 43 . 4 – 3
= (43 . 4) – 3
= 45
c)
12 : {400 : [500 – (125 + 25 . 7)}
= 12 : {400 : [500 – (125 + 175)}
= 12 : (400: 200)
= 12 : 2
= 6
d)
168 + {[2.(24 + 32) - 2560] : 72}.
= 168 + [2 . (16 + 9) – 1] : 49
= 168 + 49: 49
= 168 + 1
= 167
a) \(x^3-\frac{4}{25}x=0\)
\(\Leftrightarrow x\left(x+\frac{2}{5}\right)\left(x-\frac{2}{5}\right)=0\)
<=> x = 0
Xét 2 trường hợp:
\(\Leftrightarrow x+\frac{2}{5}=0\)
\(x=0-\frac{2}{5}\)
\(x=-\frac{2}{5}\)
\(\Leftrightarrow x-\frac{2}{5}=0\)
\(x=0+\frac{2}{5}\)
\(x=\frac{2}{5}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=\pm\frac{2}{5}\end{cases}}\)
b) \(\left(\frac{3}{8}+\frac{-3}{4}+\frac{7}{12}\right):\frac{5}{6}+\frac{1}{2}\)
\(=\left(\frac{3}{8}+\frac{-3}{4}+\frac{7}{12}\right):\frac{4}{3}\)
\(=\frac{13}{40}:\frac{4}{3}\)
\(=\frac{39}{120}=\frac{13}{40}\)
c) \(4\left(\frac{-1}{2}\right)^3-2\left(\frac{-1}{2}\right)^2+3\left(\frac{-1}{2}\right)-1\left(\frac{-1}{2}\right)^0\)
\(=4\left(\frac{-1}{2}\right)^3-2\left(\frac{-1}{2}\right)^3+3\left(\frac{-1}{2}\right)-1.1\)
\(=-\frac{1}{2}-\frac{1}{2}-\frac{3}{2}-1.1\)
\(=-\frac{5}{2}-1\)
\(=-\frac{7}{2}\)
(x2-1)2=9
=> x2-1 = 3
x2 = 3+1
x2 = 4
=> x2 = 4 = 22 ( x2=22 )
<=> x = 2
12:{390:[5.102-(53+x.72)]} = 4
390:[5.102-(53+x.72)] = 12:4
390:[5.102-(53+x.72)] = 3
5.102-(53+x.72) = 390 : 3
5.102-(53+x.72) = 130
=> 500-(125+x+49)=130
125+x+49 = 500-130
125+x+49 = 370
125+x = 370-49
125+x = 321
x = 321-125
x = 106
53(3x+2):13=103:(135:134)
53(3x+2):13=103:13
53(3x+2):13= 1000/13
125(3x+2):13 = 1000/13
125(3x+2) = 1000/13 . 13
125(3x+2) = 1000
3x+2 = 1000:125
3x+2 = 8
3x = 8-2
3x = 6
x = 6:3
x = 2
\(\left(1+2^2+2^3+....+2^{10}\right)\cdot\left(3^2\cdot2^4-12^2\right)\)
\(=\left(1+2^2+2^3+....+2^{10}\right)\cdot\left(3^2\cdot2^{2\cdot2}-12^2\right)\)
\(=\left(1+2^2+2^3+....+2^{10}\right)\cdot\left(3^2\cdot2^2\cdot2^2-12^2\right)\)
\(=\left(1+2^2+2^3+...2^{10}\right)\cdot\left[\left(3\cdot2\cdot2\right)^2-12^2\right]\)
\(=\left(1+2^2+2^3+....+2^{10}\right)\cdot\left[12^2-12^2\right]\)
\(=\left(1+2^2+2^3+...+2^{10}\cdot0\right)\)
\(=0\)